Effect of UV-B radiation on the contents of UV-B absorbing compounds and photosynthetic parameters in Parmotrema austrosinense from two contrasting habitats - Barták, M. (2018)
We studied the resistance of Parmotrema austrosinense to UV-B stress. We focused on the effects of a high dose UV-B radiation on the content of chlorophylls, carotenoids and UV-B screening compounds. Photosynthetic parameters were measured by chlorophyll fluorescence (potential and effective quantum yields, photochemical and non-photochemical quenching) and evaluated in control and UV-B-treated lichens. Lichens from two different locations in Cordoba, Argentina, were selected: (i) high altitude and dry plots at (Los Gigantes) and (ii) lowland high salinity plots (Salinas Grandes). UV-B treatment led to a decrease in the content of photosynthetic pigments and UV-B screens (absorbance decrease in 220–350 nm) in the samples from Salinas Grandes, while in Los Gigantes samples, an increase in UV-B screen content was observed. Chlorophyll fluorescence parameters showed a UV-B-induced decline in FV/FM, ΦPSII and qP indicating limitation of primary photosynthetic processes in photosystem II (PSII) of symbiotic alga, more pronounced in Salinas Grandes samples. Protective mechanism of PSII were activated by the UV-B treatment to a higher extent in samples from Salinas Grandes (NPQ 0.48) than in Los Gigantes samples (NPQ 0.26). We concluded that site-related characteristics, and in particular different UV-B radiation regimen, had a strong effect on resistance of the photosynthetic apparatus of P. austrosinense to UV-B radiation.